Aggressive Periodontitis and its Multidisciplinary Focus: Review of the Literature - Frías-Muñoz DDS, Maribel; Araujo-Espino DDS, MSc, PhD, Roxana; Martínez-Aguilar DDS, MSc, Víctor Manuel; Correa Alcalde DDS, Teresina; Aguilera-Galaviz DDS, MSc, PhD, Luis Alejandro; Gaitán-Fonseca DDS, MSc, PhD, César (Odovtos - International Journal of Dental Sciences, 2017)
The purpose of this review is to have a current prospect of periodontal diseases and, in particular, aggressive periodontitis. To know its classification and clinical characteristics, such as the extent and age group affected, as well as its distribution in the population, etiology, genetic variations, among other factors that could affect the development of this disease. Also, reference is made to different diagnostic options and, likewise, the current treatment options.